Orthotopic Liver Transplantation in Human-Immunodeficiency-Virus-Positive Patients in Germany. (16th May 2012) - Anadol, E.; Beckebaum, S.; Radecke, K.; Paul, A.; Zoufaly, A.; Bickel, M.; Hitzenbichler, F.; Ganten, T.; Kittner, J.; Stoll, M.; Berg, C.; Manekeller, S.; et al.
Abstract : Objectives . This summary evaluates the outcomes of orthotopic liver transplantation (OLT) of HIV-positive patients in Germany. Methods . Retrospective chart analysis of HIV-positive patients, who had been liver-transplanted in Germany between July 1997 and July 2011. Results . 38 transplantations were performed in 32 patients at 9 German transplant centres. The reasons for OLT were end-stage liver disease (ESLD) and/or liver failure due to hepatitis C (HCV) (n = 19 ), hepatitis B (HBV) (n = 10 ), multiple viral infections of the liver (n = 2 ) and Budd-Chiari-Syndrome. In July 2011 19/32 (60%) of the transplanted patients were still alive with a median survival of 61 months (IQR (interquartile range): 41–86 months). 6 patients had died in the early post-transplantation period from septicaemia (n = 4 ), primary graft dysfunction (n = 1 ), and intrathoracal hemorrhage (n = 1 ). Later on 7 patients had died from septicaemia (n = 2 ), delayed graft failure (n = 2 ), recurrent HCC (n = 2 ), and renal failure (n = 1 ). Recurrent HBV infection was efficiently prevented in 11/12 patients; HCV reinfection occurred in all patients and contributed considerably to the overall mortality. Conclusions . Overall OLT is a feasible approach in HIV-infected patients with acceptable survival rates in Germany. Reinfection with HCV still remains a major clinical challenge in HIV/HCV coinfection after OLT.